Aerosol shortwave direct radiative effect and forcing based on MODIS Level 2 data in the Eastern Mediterranean (Crete) - N. Benas; N. Hatzianastassiou; C. Matsoukas; A. Fotiadi; N. Mihalopoulos; I. Vardavas (Atmospheric Chemistry and Physics, 2011)
The shortwave (SW) radiation budget was computed on a 10 km × 10 km resolution above FORTH-CRETE AERONET station in Crete, Greece, for the 11-year period from 2000 to 2010. The area is representative of the Eastern Mediterranean region, where air pollution and diminishing water resources are exacerbated by high aerosol loads and climate change. The present study aims to quantify the aerosol direct effect and forcing on the local surface and atmospheric energy budget. A radiative transfer model was used, with climatological data from the Moderate Resolution Imaging Spectroradiometer (MODIS), on board NASA's Terra and Aqua satellites. The instantaneous radiative fluxes were computed for satellite overpass times at the surface, within the atmosphere and at the top of atmosphere (TOA). Downward surface fluxes and aerosol input data were validated against ground measurements. Output fluxes reveal the direct radiative effects of dust events, with instantaneous values reaching up to −215, 139 and −46 Wm−2 at the surface (cooling), within the atmosphere (warming) and at TOA (cooling), respectively. Mean monthly values show a decreasing trend of the aerosol direct radiative effect, in agreement with a similar trend in AOT. The analysis of the contribution of anthropogenic and natural aerosol show major peaks of natural aerosol direct effect occurring mainly in spring, while a summer maximum is attributed to anthropogenic aerosol. During their peaks, anthropogenic aerosol forcing can reach values of −24 Wm−2 at the surface, 19 Wm−2 in the atmosphere and over −4 Wm−2 at TOA (monthly mean instantaneous values). The corresponding monthly peak values for natural aerosol are over −20 Wm−2, 12 Wm−2 and −9 Wm−2.